Mekanisme Pertimbangan Perhitungan PBB pada Objek Pajak Bandara - Vicy Andriany; Veny Rinalny; Annisa Desfikasari (International Forum of Researchers and Lecturers, 2025)
The aim of the research is to determine the basic considerations in calculating PBB for Regional Governments/Regency Governments. This research is field research. Data collection techniques were carried out using literature studies. To carry out airport assessments, the Cost Approach is used. The assessment approach is carried out by adding up the Land Market Value indication, Building Market Value indication and Facility Component Market Value indication. The research results show that the assessment for airport PBB is not just a taxation instrument, but also a form of regional economic development. With good consideration and calculations for a PBB at the airport, this will provide great benefits and impacts for the government and surrounding communities.